1992
DOI: 10.1002/1097-4679(199201)48:1<72::aid-jclp2270480111>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the WAIS-R with psychiatric inpatients

Abstract: WAIS‐R subtest and composite scale reliabilities, standard errors of measurement, and standard errors of estimate were determined for a sample of psychiatric inpatients (N = 100). For Digit Span and Digit Symbol, test‐ retest stability coefficients were obtained; split‐half reliability coefficients were calculated for all other subtests. With the exception of Object Assembly (rxx =.38), all subtest and composite scale reliability coefficients were large and acceptable. Based on the standard error of measure, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
0
6
1
Order By: Relevance
“…In contrast, Mintzer et al (2005) reported no significant differences on the Digit Symbol Substitution Test (DSST) in abstinent opiate addicts, relative to controls. Both the WAIS-R Vocabulary Test and DSST are considered indicative of general cognitive functioning (Wechsler, 1997;Boone, 1992;Swan et al, 1995). Possible explanations for the discrepancy in our findings and those of Mintzer include possible confounding effect of illicit drug use (Davis et al, 2002), non-exclusion of subjects with positive urine toxicologies (Mintzer et al, 2005) and variations in the length of opiate abstinence (Davis et al, 2002;Mintzer et al, 2005).…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, Mintzer et al (2005) reported no significant differences on the Digit Symbol Substitution Test (DSST) in abstinent opiate addicts, relative to controls. Both the WAIS-R Vocabulary Test and DSST are considered indicative of general cognitive functioning (Wechsler, 1997;Boone, 1992;Swan et al, 1995). Possible explanations for the discrepancy in our findings and those of Mintzer include possible confounding effect of illicit drug use (Davis et al, 2002), non-exclusion of subjects with positive urine toxicologies (Mintzer et al, 2005) and variations in the length of opiate abstinence (Davis et al, 2002;Mintzer et al, 2005).…”
Section: Discussioncontrasting
confidence: 50%
“…For psychiatric inpatients, performance on Digit Span may be affected further by the presence of positive psychotic symptomatology or associated side effects from antipsychotic medications. Although Boone (1992) reported a test-retest reliability coefficient on Digit Span for a group of psychiatric inpatients that was comparable to that reported for the standardization group, wide fluctuations in scale scores (up to 4 scale points) occasionally were obtained on a case-by-case basis. Thus, the clinician who is using the Kaufman triad with psychiatric inpatients must be particularly attentive to the patient's readiness for and receptivity to this particular subtest.…”
Section: Discussionmentioning
confidence: 61%
“…While few studies have found less retest effects in patients than controls, 40 most have found similar retest effects over both short and long time intervals. 38,41,42 In a longitudinal design, Heaton and colleagues 38 found similar retest effects in schizophrenic patients as healthy controls, interestingly regardless of level of psychopathological symptoms and clinical state. Covert, procedural learning seems to be one of the few neuropsychological domains in which schizophrenic patients are not particularly impaired.…”
Section: Retest Effectsmentioning
confidence: 93%